Superstars : Das Prinzip Prominenz : Von Warhol bis Madonna. - Bronfen, Elisabeth; Brugger, Ingried; Dusini, Matthias; Eipeldauer, Heike; Franck, Georg; Grissemann, Stefan; Matt, Gerald; Mattl, Siegfried; Miessgang, Thomas; Steininger, Florian; Zeiller, Martin; Kunsthalle Wien, Wien (Wien : Kunsthalle Wien, 2006)
Andessner, Irene ; Attersee, Christian Ludwig ; Barney, Matthew ; Beuys, Joseph ; Bijl, Marc ; Blum, Michael ; Botero, Fernando ; Bradley, Slater ; Brecht, George ; Breitz, Candice ; Calle, Sophie ; Cattelan, Maurizio ; Chatwick, Casale ; Christo ; Dalton, Jennifer ; Doisneau, Robert ; Droese, Felix ; Duchamp, Marcel ; Eggleston, William ; Emin, Tracey ; Eva & Adele ; Faunce, Justin ; Fischer, Nina & Sani, Maroan el ; Fleury, Sylvie ; Fraser, Jacqueline ; Fuchs, Dieter ; G.R.A.M. ; Galella, Ron ; Geiger, Marcus ; Gil & Moti ; Gilbert & George ; Gonzales, Wayne ; Gordon, Douglas ; Graham, Rodney ; Gursky, Andreas ; Halsman, Philippe ; Hanley, Kevin ; Helnwein, Gottfried ; Herrmann, Matthias ; Hildebrandt, Volker ; Holzer, Jenny ; Horowitz, Jonathan ; Immendorff, Jörg ; Jackson, Alison ; Kauper, Kurt ; Klein, Steven ; Komad, Zenita ; Koons, Jeff ; van Lamsweerde, Inez ; Laurette, Matthieu ; Lawler, Louise ; Leibovitz, Annie ; Lüpertz, Markus ; Lüthi, Urs ; Maciejowski, Marcin ; Magritte, René ; Malevich, Kasimir ; Man Ray ; Manzoni, Piero ; Matadin, Vinoodh ; McCarthy, Paul ; McEwen, Adam ; McMullan, Patrick ; Meese, Jonathan ; Melgaard, Bjarne ; Michals, Duane ; Ming, Yan Pei ; Morimura, Yasumasa ; Newton, Helmut ; Oldenburg, Claes ; Oppenheim, Dennis ; Orlan ; Paik, Nam June ; Peyton, Elizabeth ; Pfeiffer, Paul ; Picasso, Pablo ; Prince, Richard ; Rauschenberg, Robert ; Rotella, Mimmo ; Ruscha, Ed ; Sachs, Tom ; Sander, Karin ; Sedowick, Edie ; Shaw, Jim ; Sherman, Cindy ; Starr, Georgina ; Stern, Bert ; Sturtevant, Elaine ; Sussman, Eve ; Szeemann, Una ; Taylor-Wood, Sam ; Tillmans, Wolfgang ; Tot, Endre ; Tranquilli, Adrian ; Tsilidis, Christina ; Turk, Gavin ; Uklanski, Piotr ; Ulrichs, Timm ; Vezzoli, Francesco ; Warhol, Andy ; Wasser, Julian ; Weegee ; etc.
Superstars : Von Warhol bis Madonna, Kunsthalle Wien, Wien, 2005-11-04. 2006-02-22
boek